2023
DOI: 10.1097/jnr.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Professional Nursing Practice Environment and Work Engagement: The Mediating Roles of Self-Efficacy and Achievement Motivation

Abstract: Background The shortage of nurses is a global problem. Increasing the level of work engagement is known to effectively reduce turnover rate among nursing staff. Strategies to improve work engagement based on the job demands–resources model may effectively improve nurses' job satisfaction and reduce staff turnover. Purpose A job demands–resources model was used in this study to test the hypothesis that work engagement is affected by both external resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Huang’s results were similar to the findings concerning the role of meaning in life in the chained-mediation in the present study. In addition, studies confirmed that meaning in life and the feeling of well-being were correlated [ 90 , 91 ]. The present study provided theoretical implications for future investigations on the role of meaning in life and subjective well-being in the relationship between social support and professional identity.…”
Section: Discussionmentioning
confidence: 96%
“…Huang’s results were similar to the findings concerning the role of meaning in life in the chained-mediation in the present study. In addition, studies confirmed that meaning in life and the feeling of well-being were correlated [ 90 , 91 ]. The present study provided theoretical implications for future investigations on the role of meaning in life and subjective well-being in the relationship between social support and professional identity.…”
Section: Discussionmentioning
confidence: 96%
“… 37 Also, self-efficacy partially mediates the correlation between ‘professional nursing practice environment and engagement’. 37 Dan, Huang, Ren, Tian, He 38 Cabrera-Aguilar, Zevallos-Francia, Morales-García, Ramírez-Coronel, Morales-García, Sairitupa-Sanchez, Morales-García 37 Al Hamdan, Bani Issa 39 Optimism Positive correlation with work engagement. Optimism has a mediate role between autonomy and organizational citizenship behavior.…”
Section: Resultsmentioning
confidence: 99%
“… Mediated role: The correlation between professional nursing practice environment and work engagement is partially mediated by achievement motivation. 38 Also, the interrelationship between job resources, work engagement, and burnout is mediated by intrinsic motivation. 43 Dan, Huang, Ren, Tian, He 38 Kohnen, De Witte, Schaufeli, Dello, Bruyneel, Sermeus 43 Core self-evaluation Self and control abilities predict work engagement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations